AN AGE-OLD PROBLEM IN A HIGH-TECH WORLD: THE DIGITAL HEALTH CARE DIVIDE FOR ELDERLY PATIENTS - Zofia Botto; Barbara Reizer; Marzena Swojnóg; Klaudia Krystek; Patrycja Felisiak; Dominika Kowalczyk; Dominika Bieszczad; Magdalena Barczewska; Zofia Śliwa; Dominik Andrzej Ślazyk (International Journal of Innovative Technologies in Social Science, 2026)
The rapid digitalization of health care, propelled by the COVID-19 pandemic, has led to a rapidly growing gap in use of medical technology for senior patients. The inclusion of wearable medical devices, patient portals, telemedicine, and access to information has created an opportunity for patients to have more control over their health than ever before. However, for elderly patients it also comes with new challenges due to fear or reluctance to use advanced technologies they are not familiar with, leaving them to rely on family members and caregivers. It was found  that health care provider’s hesitation in offering digital options and the expenses associated with digital devices are another obstacle. There is a significant need for modification in health care personnel attitudes regarding technology, promotion of combining community centers and health care for improving overall quality of life and digital literacy, and advocacy for senior patients' opinions when creating new medical technology and possibly incorporating AI technology to aid in bridging the gap.